Analisis Permasalahan Pembuatan Rencana Pelaksanaan Pembelajaran (RPP) Tematik Kelas IV di SDS YKPP Lirik - Putri, Dwi Rizkiana; Putra, Elpri Darta (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to describe; Knowing the problems of making the fourth grade thematic Learning Implementation Plan (RPP) at SDS YKPP Lyrics, Knowing how the solutions were made by the teacher to overcome the problems of making the fourth grade thematic Learning Implementation Plan (RPP) at SDS YKPP Lyrics. This research use desciptive qualitative approach. The data sources of this study were two fourth grade teachers and one principal. This research was conducted in the fourth grade of SDS YKPP Lyric which is located on JL. Ukui No.1 Lyrics Area Lyrics District, Indragiri Hulu Regency. data collection techniques in this study are; interviews, observations, and documentation. While the analysis of research data using the Miles & Huberman model which includes data reduction, presentation, and drawing conclusions. The results showed that the Problem Analysis of Making Class IV Thematic Learning Implementation Plans (RPP) at SDS YKPP Lyrics: (a) The problems of making Class IV thematic Learning Implementation Plans (RPP) at SDS YKPP Lyrics were limited time, lack of understanding of RPP components, difficulty determining learning strategies and learning media. (b). The solution that the teacher does to overcome the problem of making the thematic Learning Implementation Plan (RPP) for grade IV at SDS YKPP Lyric is to add additional information, attend training activities, or workshops, refer to the teacher's handbook, conduct discussions with colleagues.